2017
DOI: 10.1038/s41598-017-15290-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells internalize Mycobacterium tuberculosis through scavenger receptors and restrict bacterial growth through autophagy

Abstract: Human mesenchymal stem cells (MSCs) express scavenger receptors that internalize lipids, including oxidized low-density lipoprotein (oxLDL). We report that MSCs phagocytose Mycobacterium tuberculosis (Mtb) through two types of scavenger receptors (SRs; MARCO and SR-B1), as blockade of the receptors with antibodies or siRNA knockdown decreased the uptake of Mtb. MSCs also expressed mannose receptor (MR) that was found to endocytose rhodamine-labeled mannosylated BSA (rMBSA), though the receptor was not involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 75 publications
(113 reference statements)
2
59
0
2
Order By: Relevance
“…Previously, we and others have shown that MSCs are associated with nonreplicating M. tuberculosis (9,10,13). Therefore, we sought to determine whether MSCs are a natural reservoir for M. tuberculosis and dormancy that renders nonresponsiveness to antibiotic treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we and others have shown that MSCs are associated with nonreplicating M. tuberculosis (9,10,13). Therefore, we sought to determine whether MSCs are a natural reservoir for M. tuberculosis and dormancy that renders nonresponsiveness to antibiotic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, dormant forms of the bacteria generally do not respond to antibiotics, and where and how they evade drugs and detection is incompletely understood. Nevertheless, studies, including our previously published data, have indicated that MSCs represent a major niche for dormant TB (9,10,13). Based on these considerations, we hypothesized that M. tuberculosis acquires dormancy and thereby drug nonresponsiveness in MSCs.…”
Section: Introductionmentioning
confidence: 91%
“…Мезенхимальные стволовые клетки человека (MSCs) экспрессируют на своей поверхности два типа скавенджер-рецепторов: MARCO и SR-B1, с помощью которых индуцируют фагоцитоз M. tuberculosis. Продемонстрировано, что размножение M. tuberculosis в MSCs не происходит вследствие аутофагии и продукции NO [52].…”
Section: скавенджер-рецепторыunclassified
“…This "trained immunity" does not resemble immunological memory of adaptive immune cells, i.e., T and B cells, but rather pre-programing of cells that will respond with similar effector molecules to subsequent challenge driven by recognition of pathogen-/danger-associated molecular patterns (PAMPs/ DAMPs) by pathogen-recognition receptors (PRRs), such as Toll-like receptors (TLRs) (Gourbal et al, 2018). Stromaassociated mesenchymal stromal cells (MSC) and fibroblasts, which can also harbor pathogens (Das et al, 2013;McCormack et al, 2013;Beamer et al, 2014;Khan et al, 2017), are equipped with the capacity to present antigens to T cells via the human leukocyte antigen (HLA) class I and class II pathways during inflammation (Ilangumaran et al, 2002;Romieu-Mourez et al, 2007;Morandi et al, 2008;Das et al, 2013;Crowley et al, 2018;Hamada et al, 2019), and have been discussed to possess trained immunity characteristics (Hamada et al, 2019).…”
Section: Introductionmentioning
confidence: 99%